PENGUATAN PENDIDIKAN KARAKTER PADA EKSTRAKULIKULER SENI TARI TRADISIONAL DI SEKOLAH DASAR - Lutfi Anjar Yogi Pratiwi; Anggita Dwi Saputri; Eko Handoyo; Indriana Eko Armaidi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Culture-based character education is an urgent need that must be realized in order to foster generations that are religious and cherish local cultural wisdom. This study employs a descriptive qualitative research method. This method was used to determine whether the implementation of traditional dance extracurricular activities can foster culture-based character education at an elementary school in Blitar City. To obtain data for this research, three data collection techniques were used: observation, interviews, and documentation. Culture-based character education encompasses three aspects: moral knowing, moral feeling, and moral action. As a benchmark for success in shaping cultural character, this study concludes that the traditional dance extracurricular program has been successful because its implementation incorporates these three moral dimensions: moral knowing (analyzing, recognizing, and critically evaluating), moral feeling (empathy), and moral action (students’ creativity in making their own costumes). Keywords:extracurricular activities; character education; traditional arts; traditional dance; dance